2011
DOI: 10.5799/ahinjs.02.2011.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis with p-ANCA-associated renal failure, leukocytoclastic vasculitis and endocarditis: Case report

Abstract: The relationship between brucellosis and p-antinuclear cytoplasmic antibody (p-ANCA)-associated vasculitis (pAAV) is a rare condition. Herein, we report a 52-year-old man who was diagnosed as rapidly progressive glomerulonephritis (RPGN) and endocarditis due to brucellosis. He was treated with antimicrobial agents, steroids, plasmapheresis, renal replacement therapy and aortic valve replacement. According to our best of knowledge, no similar case has been reported previously in the literature in regard to p-AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Vasculitis is a lethal picture of brucellosis with systemic organ involvement. Turgay et al [7] reported 52-year-old male with Brucella infection and ANCAassociated vasculitis that induced rapidly progressive glomerulitis. The patient had endocarditis with vegetation on the aortic valve and leukocytoclastic vasculitis.…”
Section: Vasculitis In Brucellosismentioning
confidence: 99%
“…Vasculitis is a lethal picture of brucellosis with systemic organ involvement. Turgay et al [7] reported 52-year-old male with Brucella infection and ANCAassociated vasculitis that induced rapidly progressive glomerulitis. The patient had endocarditis with vegetation on the aortic valve and leukocytoclastic vasculitis.…”
Section: Vasculitis In Brucellosismentioning
confidence: 99%